Symbiosis between Caravanserai in Islamic Civilisation and Tourism in Modern Era: A Reference to Malaysia - Sidik@Mat Sidek, Roziah; Samsudin, Aina Zafirah Samsudin; Rozali, Ermy Azziaty; Md Lateh @ Junid, Hanif; A/L Valbir Singh, Dalbir Singh; Mohd Isa, Ammalina Dalillah (Journal of Al-Tamaddun, 2023)
Caravanserai refers to the accommodation for travelers to rest and enjoy the services provided there. Initially, it was known as ribat and khanqah. Its construction in Islamic civilisation is linked to tourism, which in turn generates the national economy. Besides that, its construction is made up of specific architecture. Thus, it is useful to promote the uniqueness of the country’s art, culture, and heritage as the main catalyst for the growth of the country’s tourism and cultural sector. The objective of this study was to examine the relationship between caravanserais in Islamic civilisation and the tourism industry, and how it can be used to promote art, cultural, and national heritage tourism in Malaysia. The study presented a qualitative research design using historical study and content analysis approach. The sampling of the study was done in two stages, namely article search based on the use of keywords such as caravanserai, Islamic tourism, art tourism, cultural tourism, and Islamic civilsation, and review of the reference list at the end of the articles that were referred to in the early stages. Meanwhile, data analysis was also conducted in stages, i.e., the analysis of the written content followed by the implied content. The research findings showed that caravanserai has a significant relationship with the tourism industry in Islamic civilisation based on three things. First, its position is on the Silk Road, which was a trade and tourism route at that time. Second, the caravanserai is a tourist attraction because it has historical places and functions as a commercial center. Third, the caravanserai contributes to the economic growth of the country as it successfully attracts many tourists to visit the place. The research findings also indicated that the caravanserai can be used to promote art, cultural, and national heritage tourism in Malaysia based on its construction as a historical monument that displays certain arts and becomes a tourist destination for local history and cultural exploration. This finding is also supported by previous studies which agreed that culture and art can be used to promote tourism. Thus, the concept of caravanserai construction in Islamic civilistion can be utilised towards promoting the tourism industry in Malaysia in line with the National Tourism Policy (NTP) 2030, which, among other things, focuses on the keystones to improve the experience and satisfaction of tourists.